“A Megcsalt Férj” or Cunningly Lingual Wives in Hungarian Ballad Tradition - Vasvári, Louise O. (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2021)
In this report I shall study one widely circulating European ballad tradition concerning wifely infidelity, to illustrate that although details among versions are temporally and culturally variable, they all belong to one narrative deep structure having to do with “cunningly lingual” wives and cuckolded husbands. These adulterous wives are a subcategory of the persistent antifeminist stereotype of the “unruly woman,” whose too active mouth, whether its voraciousness, garrulousness, or verbal cunning, implies bodily misrule, a topsy-turvy displacement of a woman’s even more fearful orifice, the vagina. I will mention noteworthy highlights from several ballad traditions, but I will concentrate on the Hungarian corpus. Through a gender-conscious reading, I will show that these retold tales that pretend to be about conjugal relations are merely another variant of misogynist male discourse on women, where the “misogyny reveals far more about masculinity and male views of the feminine than about real women” [Gaunt 1995: 71]. In addition, hegemonic masculinist interpretations, including by scholars, have been complicit in a directed reading away from the misogyny.